ONE TASK OF MODELING OF THE SPACECRAFT ONBOARD CONTROL SYSTEM - Spiridonov, V.; Razghonov, S. (Systems and Technologies, 2018)
In the subsystem of forming of command-program information the approach consisting in the task decision of spacecraft onboard systems states prognosis for the formed control program on a model is realized. The modeling results are intended for the presentation of complete information about the spacecraft onboard systems states to the operators of control sector during the normal spacecraft control, to the control transfer by duty groups, analysis of abnormal situations. Summarizing the results it can be argued that the modeling of the deterministic component of control program of various space crafts with program-coordinate control is possible in principle. It is also possible modeling of programs of onboard control system operating in abnormal situations. There is a limitation due to the inability to accurately predict the manner and time of their occurrence. However, when abnormal situations take place and the onboard control system has executed their parrying this information may be obtained in the «OCS report». As a result of analysis of the report, the operator can manually correct the states of the corresponding elements in the model of onboard equipment. In that case the OCS cannot alone perform the parrying of abnormal situation the onboard equipment state information at a given time can be transmitted to ground control center. It is necessary to perform the analyze of abnormal situation and take appropriate measures to parrying it due to the actual and forecasted information about the functioning of onboard equipment. Therefore, this restriction does not preclude to the using of the proposed methodology for the spacecraft program- coordinate control. The modeling algorithm of forming of the control program determined constituent offers. The actions of control sector operators are considered in that case of abnormal situations appearance when control decisions are made by the spacecraft onboard control system. The areas development of application of predictive models on-board equipment to solve the problems of analysis, decision-making and parrying of abnormal situations in the spacecraft control circuit is a perspective area of research.